A patient-centred check sheet improves communication on the trauma ward round. (2nd August 2019) - Brown, Oliver S; Toi, Teri HH; Barbosa, Pedro R; Pookarnjanamorakot, Patra; Trompeter, Alex
Abstract : Background: Effective communication on surgical ward rounds should clarify for patients their management plan and answer questions adequately. Pressures on time conspire against this interchange of information. A patient-centred surgical communication check sheet was devised to enable rapid two-way transfer of information between surgeon and patient. Methods: A quality improvement project involved three cycles. Through the use of a patient survey, distributed following the daily ward round, areas for improvement in communication were highlighted in cycle one. The surgical communication check sheet was introduced in cycle two, and modified before cycle three following discussion with the orthopaedic department. The surgical communication check sheet was handed out to patients before the ward round, and its efficacy was measured by evaluating ward round communication using the survey as in cycle one. Results: Initial results showed a variable standard of communication, which improved following the introduction of the surgical communication check sheet in cycle two. In cycle three, 84.7% patients felt that the check sheet aided communication on the ward round. Measures of communication improved between cycles one and three: the percentage of patients with unanswered questions fell from 21.8% to 16.7%, the number of patients unsure why a test was done fell from 25.9% to 12.7%, and average understanding of the management plan rose from 64.7% to 83.3%. Conclusions: The introduction of the surgical communication check sheet improved ward round communication, and was welcomed by almost 85% of patients. Accounts from patients indicate two benefits of the check sheet: the surgeon is immediately aware of a patient with questions or concerns, allowing these to be adequately addressed, and patients can formulate questions before the ward round which bolsters their confidence to ask them.